Immunocytochemical localization of the guanine nucleotide-binding protein Go in primary cultures of neuronal and glial cells - Brabet, P (J Neurosci, 1988)
We have localized the guanine nucleotide-binding protein, Go, in primary cultures of pure neuronal and glial cells prepared from different mouse brain areas. Immunoblotting experiments with selective affinity-purified polyclonal rabbit antibodies to the 39 kDa alpha subunit of Go (Go alpha) indicated that Go is distributed in both neurons and glial cells. Go alpha accounts for 0.3% of total membrane proteins in striatal neurons. High specific Go immunoreactivity was also detected in cortical neurons and cerebellar granule cells. Similarly, striatal glial cells contain large amounts of Go (0.2% of total membrane proteins), as do glial cells from cerebral cortex and colliculi. Surprisingly, Go was barely detectable in cerebellar glial cells. 32P-ADP-ribosylation of the same neuronal and glial cell membranes with pertussis toxin indicated the presence of at least 3 substrates related to Go alpha, Gi alpha (41 kDa), and a 40 kDa protein. This 40 kDa protein is the major pertussis toxin substrate in glial cells, while Go alpha is predominant in neuronal membranes. Confirming immunoblotting, no labeled band was detected at 39 kDa in cerebellar glial cells with pertussis toxin. Indirect immunofluorescence staining of cerebellar granule cells and striatal neurons with purified Go alpha antibodies was pronounced at the plasma membrane level, particularly at cell-cell contact areas, and in neurite arborization. More discrete staining was also apparent in the cytoplasm, whereas nuclei remained unstained. In striatal glial cells, specific immunolabeling was more diffused over the whole cell, and dense around the nucleus. The localization of Go suggests that this protein must perform important functions in both the neuronal and glial cells that are discussed.